Online System for Cash Inflows and Outflows Management at PT Rizma Tour & Travel - Monika Handayani; Fitria Fitria; Noor Salsabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PT Rizma Tour & Travel is a company operating in the travel agency sector. The problem in this research is that recording cash receipt and disbursement transactions still uses a manual and semi-computerized system using Microsoft Excel to create cash receipt and disbursement reports. This problem can result in incorrect recording or incorrect input of transactions, resulting in inaccurate cash receipt and disbursement reports.The research method used in this research is qualitative research with a case study approach. This research aims to build a cash receipt and disbursement application for PT Rizma Tour & Travel which is used to assist in recording cash receipt and disbursement transactions.The results of this research are in the form of a web-based application for cash receipts and disbursements that can help PT Rizma Tour & Travel in recording cash receipt and disbursement transactions so that they run effectively and efficiently, including creating cash receipt and disbursement reports.